Neutrophils dominate in opsonic phagocytosis of P. falciparum blood-stage merozoites and protect against febrile malaria - Garcia-Senosiain, A.; Kana, I.H.; Singh, S.; Das, M.K.; Theisen, M.; Adu, B.; Hertegonne, S.; Dziegiel, M.H. (Communications Biology, 2021)
Antibody-mediated opsonic phagocytosis (OP) of Plasmodium falciparum blood-stage merozoites has been associated with protection against malaria. However, the precise contribution of different peripheral blood phagocytes in the OP mechanism remains unknown. Here, we developed an in vitro OP assay using peripheral blood leukocytes that allowed us to quantify the contribution of each phagocytic cell type in the OP of merozoites. We found that CD14++CD16− monocytes were the dominant phagocytic cells at very low antibody levels and Fc gamma receptor (FcγR) IIA plays a key role. At higher antibody levels however, neutrophils were the main phagocytes in the OP of merozoites with FcγRIIIB acting synergistically with FcγRIIA in the process. We found that OP activity by neutrophils was strongly associated with protection against febrile malaria in longitudinal cohort studies performed in Ghana and India. Our results demonstrate that peripheral blood neutrophils are the main phagocytes of P. falciparum blood-stage merozoites.
Research Article
Keywords: Plasmodium falciparum; malaria; Neutrophils; phagocytes